TOWARD A NEW PARADIGM OF MARKETING Understanding Customers* - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
The rapid change of business environment as a result of technology advance is transforming choice, and choice is transforming the marketplace. Volatile environment and high competition demand businesses more sensitive to customer. Business with weak market orientation comes up as a result of poor understanding about customer needs and competition. Furthermore, understanding toward customer could affect marketing practice. This paper explores some relevant themes of understanding customers in this changing environment linked to some marketing approaches in winning the business competition. Companies must figure out about their customer and market where the businesses operate. Impact of customers' preferences could lead to shift the marketing approach. The article may conclude that understanding customers well not only concern with their needs, wants, and desire but also to overcome customer discontent by dialogue with customers, collaboration, provide some information, and co-designed by customers.